HF Radar Measurements of Surface Waves in the Gulf of Naples (Southeastern Tyrrhenian Sea): Comparison With Hindcast Results at Different Scales - Saviano, Simona; De Leo, Francesco; Besio, Giovanni; Zambianchi, Enrico; Uttieri, Marco (Frontiers in Marine Science, 2020)
HF radar systems wave measurements are evaluated against numerical simulations in the Gulf of Naples (Southeastern Tyrrhenian Sea). Wave measurements are obtained from three CODAR SeaSonde HF radars installed along the coast of the Gulf of Naples. The numerical models employed are WavewatchIII, implemented on a regional scale with a resolution of about 10 km in longitude and latitude in the whole Mediterranean Sea, and SWAN, implemented with a 200 m resolution in the area of interest. Numerical simulations are also validated against experimental data acquired by a buoy installed offshore the Gulf of Naples. The agreement between HF radar measurements and model hindcasts is evaluated through the estimate of statistical error indices for the main wave characteristics (significant wave height, mean period and mean direction). The consistency between wave parameters retrieved by HF radars and hindcasted by the models opens the way to future integration of the two systems as well as to the utilization of HF radar wave parameters that could be envisaged for data assimilation in wave models.